tính
\(\frac{1+2+2^2+2^3+...+2^{2008}}{1-2^{2009}}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có: \(B=\frac{2008}{1}+\frac{2007}{2}+\frac{2006}{3}+...............+\frac{2}{2007}+\frac{1}{2008}\)
\(B=\left(1+\frac{2007}{2}\right)+\left(1+\frac{2006}{3}\right)+........+\left(1+\frac{1}{2008}\right)+1\)
\(B=\frac{2009}{2}+\frac{2009}{3}+..............+\frac{2009}{2008}+\frac{2009}{2009}\)
\(B=2009\left(\frac{1}{2}+\frac{1}{3}+.........+\frac{1}{2009}\right)\)
Khi đó: \(\text{}\text{}\text{}\frac{A}{B}=\frac{1}{2009}\)
Chuc bạn học tốt!!
Ta có: \(B=\frac{2008}{1}+\frac{2007}{2}+\frac{2006}{3}+...+\frac{2}{2007}+\frac{1}{2008}\)
\(=2008+\frac{2007}{2}+\frac{2006}{3}+...+\frac{2}{2007}+\frac{1}{2008}\)
\(=\left(1+\frac{2007}{2}\right)+\left(1+\frac{2006}{3}\right)+...+\left(1+\frac{2}{2007}\right)+\left(1+\frac{1}{2008}\right)\)
\(=\frac{2009}{2}+\frac{2009}{3}+...+\frac{2009}{2007}+\frac{2009}{2008}\)
\(=2009\left(\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2007}+\frac{1}{2008}\right)\)
Ta có: \(\frac{A}{B}=\frac{\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2007}+\frac{1}{2008}}{2009\left(\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2007}+\frac{1}{2008}\right)}\)
hay \(\frac{A}{B}=\frac{1}{2009}\)
\(C=\frac{\frac{1}{2008}-\frac{1}{2009}-\frac{1}{2010}}{\frac{5}{2008}-\frac{5}{2009}-\frac{5}{2010}}+\frac{\frac{2}{2007}-\frac{2}{2008}-\frac{2}{2009}}{\frac{3}{2007}-\frac{3}{2008}-\frac{3}{2009}}\)
\(=\frac{\frac{1}{2008}-\frac{1}{2009}-\frac{1}{2010}}{5.\left(\frac{1}{2008}-\frac{1}{2009}-\frac{1}{2010}\right)}+\frac{2.\left(\frac{1}{2007}-\frac{1}{2008}-\frac{1}{2009}\right)}{3.\left(\frac{1}{2007}-\frac{1}{2008}-\frac{1}{2009}\right)}\)
\(=\frac{1}{5}+\frac{2}{3}\)
\(=\frac{13}{15}\)
Gọi \(1+2+2^2+2^3+...+2^{2008}\) là D.
Ta có:
\(D=1+2+2^2+2^3+...+2^{2008}\)
\(2D=2+2^2+2^3+2^4...+2^{2009}\)
\(2D-D=\left(2+2^2+2^3+2^4...+2^{2009}\right)-\left(1+2+2^2+2^3+...+2^{2008}\right)\)\(D=2^{2009}-1\)
\(B=\dfrac{2^{2009}-1}{1-2^{2009}}\\ =\dfrac{\left(-1\right)\cdot\left(1-2^{2009}\right)}{1-2^{2009}}\\ =-1\)
a) C=\(\left(1-\frac{1}{2}\right)\left(1-\frac{1}{3}\right)\left(1-\frac{1}{4}\right)...\left(1-\frac{1}{1000}\right)\)
\(C=\frac{1}{2}.\frac{2}{3}.\frac{3}{4}...\frac{999}{1000}\)\(=\frac{1.2.3...999}{2.3.4...1000}=\frac{1.\left(2.3.4....999\right)}{\left(2.3.4....999\right).1000}\)\(=\frac{1}{1000}\)
b) Đặt: A=\(1+2+2^2+2^3+...+2^{2008}\)
\(\Leftrightarrow2A=2+2^2+2^3+....+2^{2008}+2^{2009}\)
\(\Leftrightarrow2A-A=2^{2009}-1\)
\(\Leftrightarrow A=2^{2009}-1\)
\(\Rightarrow S=\frac{2^{2009}-1}{1-2^{2009}}\)\(=\frac{2^{2009}-1}{-\left(2^{2009}-1\right)}=\frac{1}{-1}=-1\)
vậy: S=(-1)
1.
\(1+\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+...+\frac{1}{2^{99}}+\frac{1}{2^{100}}+\frac{1}{2^{100}}\)
\(=1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{99}}+\left(\frac{1}{2^{100}}+\frac{1}{2^{100}}\right)\)
\(=1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{99}}+\frac{1}{2^{99}}\)
cứ làm như vậy ta được :
\(=1+1=2\)
2. Ta có :
\(\frac{2008+2009}{2009+2010}=\frac{2008}{2009+2010}+\frac{2009}{2009+2010}\)
vì \(\frac{2008}{2009}>\frac{2008}{2009+2010}\); \(\frac{2009}{2010}>\frac{2009}{2009+2010}\)
\(\Rightarrow\frac{2008}{2009}+\frac{2009}{2010}>\frac{2008+2009}{2009+2010}\)
Đặt A=1+2+22+23+...+22008
=>2A=2+22+23+24+...+22009
=>2A-A=A=(2+22+23+24+...+22009)-(1+2+22+23+...+22008)
=22009-1
Suy ra:\(\frac{1+2+2^2+2^3+...+2^{2008}}{1-2^{2009}}=\frac{2^{2009}-1}{1-2^{2009}}=\frac{-\left(1-2^{2009}\right)}{1-2^{2009}}=-1\)